Clinical, Functional and Radiological Outcome of Spinoplevic Fixation in Patients with Vertically Unstable Pelvic Fractures: A Prospective Study of 40 Cases - A. Elsherif, Eslam; A. Shoulah, Saad; E. Farag, Hossam; A. Khalil, Sherin (International Journal of Psychosocial Rehabilitation, 2020)
Background: Vertically unstable pelvic ring fractures have significant impacts on patients’ quality of life. Several techniques have been described for stabilizing posterior pelvic ring injuries, especially those with vertical shear patterns. The current study has been designed to evaluate the method of spinopelvic fixation as a method of treatment of complex vertically unstable pelvic injuries. Methods: Between 2014 and 2019, a total of 40 patients with vertically unstable pelvic fractures were treated by spinopelvic fixation at the National Bank Hospital, which is a trauma center in Cairo, Egypt. Patients were seen in follow-up, on average, for 12 months after surgery. Functional outcome was assessed using the Majeed score. Radiological outcome was evaluated by the Matta radiological scoring system. Results: The injury was unilateral in 36 patients and bilateral in 4 patients. The mean Majeed score was 82.5/100. The mean Matta radiological score for evaluating postoperative reduction showed excellent reduction in most of the patients. Screw prominence occurred in 32 patients (80%), but wound dehiscence and deep infection occurred in 5 (12.5%) and 2 (5%) patients, respectively. 9 patients (22.5%) had preoperative neurological deficit of sciatic nerve distribution. 8 of them fully recovered their neurologic deficit within the follow-up period. Conclusion: In comminuted patterns of vertical shear pelvic fractures, spinopelvic fixation proved to be an effective means for obtaining a stable, rigid fixation with an accepted rate of complications compared to other fixation methods. Wound-related problems were the most common associated complications. However, spinopelvic fixation was the only applicable method in specific fractures, especially comminuted sacral fractures with neurological deficit.